Density based Dynamic Traffic Signal Simulation using Arduino Microcontroller - S., Priyadharshini; P., Gowthamraj; S., Manikandan (Journal of Ubiquitous Computing and Communication Technologies, 2025)
The Density-Based Dynamic Traffic Signal Simulation focuses on enhancing urban traffic management by introducing a smart traffic control system that adapts signal timings based on real-time vehicle density. Conventional traffic signals operate on fixed cycles, which often lead to unnecessary delays, increased fuel consumption, and traffic congestion, especially during peak hours. This study uses Infrared (IR) sensors to detect the presence of vehicles on each road and sends the data to an Arduino microcontroller, which then dynamically adjusts the green light duration depending on traffic density. Lanes with high traffic are given longer green signals, while lanes with little or no traffic receive shorter durations, improving overall traffic flow. The entire system is simulated using Proteus Design Suite, where four IR sensors and 12 LEDs (Red, Yellow, Green) represent a typical four-way intersection. The simulation demonstrates how real-time sensor input can effectively manage traffic and reduce idle time on the roads. This solution is scalable, cost-effective, and suitable for integration into smart city infrastructure. It can be further enhanced with IoT modules, emergency vehicle detection, and cloud- based traffic analytics to create a more efficient and responsive transportation system.